2015
DOI: 10.3892/etm.2015.2751
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mitochondrial haplogroup N9a on type 2 diabetes mellitus and its associated complications

Abstract: Abstract.A case-control study was conducted with the aim of identifying the predominant haplogroups associated with type 2 diabetes mellitus (T2DM) and its complications. In addition, the role of N9a in T2DM risk and complications was analyzed. Sequencing of the entire mitochondrial DNA was conducted in 235 patients and 244 controls in cohort 1, and six haplogroups (F, B4, D4, D5, M8a and N9a) associated with T2DM were classified. The frequency of N9a was further determined in cohort 2 (440 patients and 244 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The participants without diabetes were people in whom the fasting plasma glucose concentration was ,6.1 mmol/L and blood glycosylated hemoglobin (HbA 1c ) level was ,6.2% (44 mmol/mol). We have described 675 patients and 649 control subjects used here in a previous study (27). Informed consent was obtained from all participants under protocols approved by the ethics committee of Wenzhou Medical University.…”
Section: Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants without diabetes were people in whom the fasting plasma glucose concentration was ,6.1 mmol/L and blood glycosylated hemoglobin (HbA 1c ) level was ,6.2% (44 mmol/mol). We have described 675 patients and 649 control subjects used here in a previous study (27). Informed consent was obtained from all participants under protocols approved by the ethics committee of Wenzhou Medical University.…”
Section: Study Participantsmentioning
confidence: 99%
“…Complete mtDNA sequence was Sanger sequenced for 347 T2D patients and 383 control subjects by using 24 previously reported pairs of mtDNA primers (28). The mtDNA of 235 T2D patients and 141 control subjects was completely sequenced previously (27); for all other study participants, Sanger sequencing was performed using two pairs of mtDNA primers (Supplementary Table 1). SNPs of each participant were identified by comparing the obtained sequences with the revised Cambridge Reference Sequence by using CodonCode Aligner 3.0.1 (CodonCode Corporation, Centerville, VA).…”
Section: Mtdna Sequencing and Genotypingmentioning
confidence: 99%
“…Also in the Japanese, M8a was found to be at increased risk of T2DM and B4c with predisposition to OB [25]. By contrast, in the Chinese haplogroup N9a has been found to be at increased risk of T2DM [26] and diabetic retinopathy [27]. Among Han Chinese M9 was found to be at increased risk of T2DM [28] as was M8a [27].…”
Section: Genetic Analysis Of East Asian Mtdna Variants With T2dm and Msmentioning
confidence: 99%
“…By contrast, in the Chinese haplogroup N9a has been found to be at increased risk of T2DM [26] and diabetic retinopathy [27]. Among Han Chinese M9 was found to be at increased risk of T2DM [28] as was M8a [27]. In a Taiwanese sample, haplogroups B4a1a and E2b1 were found to be significantly associated with T2DM, while haplogroup D4 was protective [29].…”
Section: Genetic Analysis Of East Asian Mtdna Variants With T2dm and Msmentioning
confidence: 99%
“…mtDNA haplogroups and their characteristic SNPs—for example, m.10398A/G [2], m.5178C/A [3], and m.152T/C [4]—can be advantageous or detrimental and have been implicated in a number of diseases and pathological conditions, including cancer [5], aging [6], diabetes [7], osteoarthritis [8], schizophrenia [9], and Leber's hereditary optic neuropathy [10]. A phylogenetic tree of L3 subhaplogroups that migrated from Africa to East Asia [11, 12] revealed that many of the subclades were associated with metabolic and degenerative diseases [13, 14]. The link between mtDNA haplogroup/SNPs and disease has been attributed to possible changes in mitochondrial reactive oxygen species (ROS) levels, respiration capacity, and ATP production [15, 16].…”
Section: Introductionmentioning
confidence: 99%